MEMORIALS AND PLACES OF MEMORIAL: LOCAL AND NATIONAL DIMENSIONS - Yaroshchuk, Inna; Sokolov, Danylo (SWorld-Ger Conference proceedings, 2025)
In contemporary Ukrainian society, which is undergoing profound sociocultural transformations, the issue of memorialization has acquired particular significance. Memorials and sites of memory function not only as spatial representations of the past but al